Market Segmentation for Wetland Micro, Small and Medium Enterprises (MSME) Products in South Kalimantan - Yeni Susanty (Cita konsultindo, 2024)
MSME products from wetlands in South Kalimantan include various commodities such as fish, shrimp, seaweed, and other processed products that have high economic value. The research aims to provide an in-depth understanding of the concepts of market recognition and market segmentation and provide recommendations and suggestions that can help MSMEs in developing their business. This research uses a qualitative research design to understand the experiences and perceptions of MSME entrepreneurs regarding market segmentation. Data was collected through in-depth interviews with 2 (two) MSME actors, questionnaire distribution to 30 MSMEs, and field observations. Data analysis was carried out using descriptive analysis. The market segmentation and effective marketing strategies can increase sales and customer satisfaction. The market analysis and selecting the right target market are also important steps in developing an effective marketing strategy. The wetland products present significant economic opportunities but also face challenges that require a balanced approach between development and conservation.